2019
DOI: 10.1038/s41598-019-43727-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathic traits are related to diminished guilt aversion and reduced trustworthiness during social decision-making

Abstract: Individuals with high levels of psychopathic tendencies tend to show a lack of guilt, a lack of empathic concern, and a disregard for the impact of their decisions on others. However, how guilt influences social decision-making for those with high psychopathic traits is still unknown. Here, we investigated how psychopathic traits relate to the capacity to acquire knowledge about social expectations, and to what extent guilt aversion affects subsequent decision-making. 63 participants completed self-report meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 52 publications
(62 reference statements)
3
32
0
Order By: Relevance
“…This might be due to a distorted perception of offer fairness, as participants from a community sample scoring high on psychopathy rated unfair offers as more fair than those scoring low on psychopathy 56 . In a recent study by Gong et al 57 , non-delinquent psychopathic individuals behaved much more profit-maximising than the psychopathic offenders in our study. The non-delinquent psychopathic individuals ignored their interaction partners’ expectations and felt less guilty when they violate them than non-delinquent subjects scoring low on psychopathy 57 .…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…This might be due to a distorted perception of offer fairness, as participants from a community sample scoring high on psychopathy rated unfair offers as more fair than those scoring low on psychopathy 56 . In a recent study by Gong et al 57 , non-delinquent psychopathic individuals behaved much more profit-maximising than the psychopathic offenders in our study. The non-delinquent psychopathic individuals ignored their interaction partners’ expectations and felt less guilty when they violate them than non-delinquent subjects scoring low on psychopathy 57 .…”
Section: Discussionsupporting
confidence: 47%
“…In a recent study by Gong et al 57 , non-delinquent psychopathic individuals behaved much more profit-maximising than the psychopathic offenders in our study. The non-delinquent psychopathic individuals ignored their interaction partners’ expectations and felt less guilty when they violate them than non-delinquent subjects scoring low on psychopathy 57 . This highlights the necessity that future work compares participants scoring high on psychopathy from a prison cohort with those from a community cohort to establish similarities and differences in norm adherence behaviour during repeated interaction decision-making paradigms.…”
Section: Discussionsupporting
confidence: 47%
“…In fact, the pooled sample size of our social punishment meta-analyses exceeded 100 individuals, making it the largest dataset to date investigating this question. Given the role that differences in the processing of social punishments may play in a wide range of neuropsychiatric disorders (such as major depressive disorder (Kumar et al, 2017) or antisocial personality disorder (Gong et al, 2019)), it seems imperative that future studies start to invest more in investigating the neural underpinnings of social punishment processing in both healthy and clinical samples. Second, our findings are limited by the reported sample demographics.…”
Section: Limitationsmentioning
confidence: 99%
“…This meta-analysis focused specifically on the anticipation social rewards (it did not examine the receipt phase of social rewards, or the processing of social punishment at all). Given the role that differences in the processing of social punishments may play in a wide range of neuropsychiatric disorders (such as major depressive disorder (Kumar et al, 2017) or antisocial personality disorder (Gong et al, 2019)), characterizing the neural underpinnings of social punishment processing in healthy samples is paramount to identify how disruption of these circuits might give rise to impairments in social cognition during pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental economic studies consistently showed that higher primary psychopathic trait was correlated with lower cooperative behaviors (20,24,31). Rilling et al (2007) found that adults scoring high on psychopathy were more likely to defect and less likely to maintain an established mutual cooperation in prisoner dilemma games (PDGs).…”
Section: Introductionmentioning
confidence: 99%